A Study on the Usage Behavior Towards Virtual Meeting Applications in Pre-During-Post Pandemic Period in India - K, Vigneshwar (Digital Repository of Theses, 2024)
Purpose This research aims to investigate the evolving usage patterns, perceptions, engagement, and post-usage behaviour of users towards virtual meeting apps in India across three distinct phases: pre-pandemic, during the pandemic, and post-pandemic. The study seeks to provide insights into how these factors change over time and their impact on user behaviour, with a focus on identifying key drivers of engagement and satisfaction. Design /Methodology Utilizing a longitudinal design, 600 respondents, were selected through purposive sampling. Data collection was conducted thrice across the three phases using a well-structured questionnaire. Statistical analysis, including descriptive techniques such as frequency and percentage analysis, mean analysis, and inferential techniques such as independent-samples t- test, one-way ANOVA, Pearson correlation, and multiple regression, were employed to examine relationships between variables over time. Findings Across the pre-pandemic, during-pandemic, and post-pandemic phases, convenience consistently emerged as a critical factor influencing user engagement, with significant correlations observed between convenience and engagement. During the pandemic, convenience exhibited an even more substantial impact on user engagement. Post-pandemic, a shift was observed in user priorities, with perceived benefits becoming the primary driver of engagement. Additionally, convenience retained its significance in fostering positive post- usage behavior across all phases, indicating its enduring importance over time. Conclusion: This longitudinal study underscores the enduring significance of convenience in driving user engagement and post-usage behavior in virtual meeting apps, highlighting the need for developers to prioritize usability and accessibility. The shift towards perceived benefits post- pandemic suggests evolving user expectations, emphasizing the importance of developers aligning their offerings with changing user needs. Insights from this research provide actionable recommendations for developers and service providers to enhance user satisfaction and engagement, ensuring the continued success of virtual meeting apps in India. The longitudinal nature of the study also offers valuable insights into the product life cycle of virtual meeting apps, guiding developers in innovating and adapting their offerings to meet evolving user needs and market dynamics across different phases of adoption and maturity.